Effect of different level of molasses inclusion on feed intake, body weight gain and carcass parameters of Afar sheep in Ethiopia - Hassen, Anwar Seid; Ali, Mohammed Yasin (Asian Journal of Medical and Biological Research, 2019)
The experiment was conducted to evaluate the effect of supplementing different levels of molasses and concentrates mix with a basal diet of cultivated pasture hay on intake, body weight and carcass quality of Afar sheep. Twenty four yearling Afar sheep, grouped in to four groups of six animals each in a randomized complete block design. The experiment consisted of four months feeding trial each group will receive the experimental feeds. Treatments were mixed concentrate + 20% inclusion molasses (T1), mixed concentrate + 15% inclusion molasses (T2), mixed concentrate + 10% inclusion molasses (T3) and 0% inclusion (T4). In this experiment with mean initial weight of 15.9±0.39 kg (mean ± SD), 16.2 ±0.41 kg, 16.3±0.42k.g and 16.1kg±0.42 respectively, were used in each treatment group. The experiment was consisted of 90 days of feeding trial followed by carcass evaluation. The concentrate mix were 2:1 (wheat bran and cotton seed cake) The CP content of the panicum antidotale hay, concentrate mix and molasses were 95g/kg DM, 252g/kg DM, and 38.4g/kg, respectively. Hay DM intake was did not differ (P<0.05) among all treatments. Average daily weight gain (ADG) was higher (P<0.05) for T2 (69.59g/kg) compared to other treatments. Hot carcass weight also higher (P<0.05) for T2 (14.41kg). Weight gains 12.31kg, 13.83kg, 11.25kg and 10.26kg for Tx1, Tx2, Tx3 and Tx4, respectively). All Carcass parameters gave advantage (P<0.01) to Tx2. From the present study, it can be concluded that Tx2 sheep performed better than Tx1, Tx3, and Tx4 in terms of body weight gain, Feed intake, and carcass parameters. Asian J. Med. Biol. Res. March 2019, 5(1): 23-30